2007
DOI: 10.1590/s0004-27492007000300014
|View full text |Cite
|
Sign up to set email alerts
|

Nível de testosterona total em mulheres pós-menopausa com olho seco

Abstract: Further research with a greater bigger sample is necessary to establish the relation of androgen levels in dry eye patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
11
0
4
Order By: Relevance
“…A testosterona regula o desenvolvimento, a diferenciação e a produção lipídica das glândulas de Meibômio e muitas dessas atuações estão na dependência de ligação com receptores de andrógenos em células acinares e consequente alteração no controle da Referências transcrição genética local 6,10 . Os estrógenos, por sua vez, estão associados com redução de tamanho, atividade das glândulas sebáceas e estimulam a liberação lisossômica de enzimas que provocam morte celular e diminuição de produção lipídica.…”
Section: Discussionunclassified
“…A testosterona regula o desenvolvimento, a diferenciação e a produção lipídica das glândulas de Meibômio e muitas dessas atuações estão na dependência de ligação com receptores de andrógenos em células acinares e consequente alteração no controle da Referências transcrição genética local 6,10 . Os estrógenos, por sua vez, estão associados com redução de tamanho, atividade das glândulas sebáceas e estimulam a liberação lisossômica de enzimas que provocam morte celular e diminuição de produção lipídica.…”
Section: Discussionunclassified
“…Women are more likely to experience DE disease during certain periods of significant hormonal alteration, for example, during pregnancy, lactation, oral contraceptive use, and after menopause, suggesting that DE may be related to sex hormones [ 36 , 37 , 38 , 39 ]. Receptors for androgens, progesterone, estrogen, and prolactin have been found in several ocular tissues, including the lacrimal gland and MG [ 36 , 37 , 38 , 39 ]. Androgens are steroid hormones that are produced by the adrenals (testosterone, androstanediol, dehydroepiandrosterone sulfate (DHEAS), dehydro-epiandrosterone (DHEA), androstenedione (A)), gonads (T), and peripheral tissues (dihydrotestosterone (DHT)).…”
Section: Methodsmentioning
confidence: 99%
“…Androgens are steroid hormones that are produced by the adrenals (testosterone, androstanediol, dehydroepiandrosterone sulfate (DHEAS), dehydro-epiandrosterone (DHEA), androstenedione (A)), gonads (T), and peripheral tissues (dihydrotestosterone (DHT)). Experimental and human studies have demonstrated that androgen levels are essential for normal lacrimal gland function and structural organization, and that prolactin and estrogen also plays an important role in providing adequate hormone provision for optimal lacrimal production [ 39 , 40 , 41 ]. In particular, the androgen receptor influences the MGs; this has led to the hypothesis that these glands are under hormonal control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As alterações que induzem a CCS são, basicamente, a ausência de atividade lacrimal e a ausência da glândula ou atrofia glandular. Clinicamente a CCS manifesta-se com secreção ocular mucoide, blefaroespasmo, hiperemia conjuntival, vascularização corneana, fibrose, pigmentação corneana, dor ocular, doença corneana progressiva e déficit de acuidade visual (Berdoulay et al, 2005;Duarte et al, 2007;Herrera, 2008). O diagnóstico é baseado nos sinais clínicos e nos resultados obtidos dos exames específicos, tais como: tempo de quebra do filme lacrimal, corantes da superfície ocular (fluoresceína, rosa bengala, lissamina verde) e teste lacrimal de Schirmer (Laus e Oriá, 1999;Herrera, 2008;Galera et al, 2009).…”
Section: Introductionunclassified